(untitled) (Research, Society and Development, 2020)
The present study aimed to perform a literature review regarding the use of Salvia officinalis in the treatment of Diabetes Mellitus, in view of the importance of glycemic control for the systemic and oral health of patients with this disease. The literature review was prepared using the Google Scholar, PubMed and Scielo platforms as a research source. From the descriptors: “Phytotherapy”, “Salvia officinalis” and “Diabetes”, 31 articles published between 2010 and 2020 were selected. Diabetes mellitus stands out as an important cause of morbidity and mortality worldwide. Several researchers have investigated the effects of Salvia officinalis against diabetes, and its traditional use as an antidiabetic can be justified by the secondary metabolisms that are present in the preparations made from this plant. Studies indicate that S. officinalis can improve glycemic control and lipid profile, being useful in the treatment of diabetic and hyperlipidemic patients. In addition, no adverse effects have been reported. Salvia officinalis has stood out for its hypoglycemic action capacity, through the activity of its various constituents, showing itself capable of reducing fasting and postprandial blood glucose in several studies, in addition to decreasing glycosylated hemoglobin, total cholesterol , triglycerides and LDL, either alone or associated with other natural compounds.